2022
DOI: 10.1101/2022.01.20.22269581
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Occurrence and transmission potential of asymptomatic and presymptomatic SARS-CoV-2 infections: update of a living systematic review and meta-analysis

Abstract: BACKGROUND Debate about the level of asymptomatic severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection continues. The amount of evidence is increasing and study designs have changed over time. We conducted a living systematic review to address three questions: (1) Amongst people who become infected with SARS-CoV-2, what proportion does not experience symptoms at all during their infection? (2) What is the infectiousness of asymptomatic and presymptomatic, compared with symptomatic, SARS-CoV-… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 205 publications
(495 reference statements)
1
6
0
Order By: Relevance
“…In 13 out of 18 studies identified, 33 34 35 36 37 41 42 43 44 45 46 47 48 suspected primary cases were asymptomatic, presymptomatic, or near the time of symptom onset when transmission occurred. This finding is consistent with wider evidence that people with asymptomatic or presymptomatic SARS-CoV-2 infection can contribute to the community spread of covid-19, 61 62 63 including from long distance airborne transmission.…”
Section: Discussionsupporting
confidence: 90%
“…In 13 out of 18 studies identified, 33 34 35 36 37 41 42 43 44 45 46 47 48 suspected primary cases were asymptomatic, presymptomatic, or near the time of symptom onset when transmission occurred. This finding is consistent with wider evidence that people with asymptomatic or presymptomatic SARS-CoV-2 infection can contribute to the community spread of covid-19, 61 62 63 including from long distance airborne transmission.…”
Section: Discussionsupporting
confidence: 90%
“…The type of studies that provide estimates of the proportion of asymptomatic SARS-CoV-2 infections and heterogeneity between them has changed over the course of the pandemic. In our living systematic review, the prediction interval has widened from 23% to 37% in studies published up to 25 March 2020 [ 23 ], to 3% to 67% up to June 2020 [ 12 ], 2% to 89% up to 2 February 2021 [ 21 ] and remains at 2% to 90% up to 6 July. We found 3 systematic reviews, in which authors reported restriction to studies with adequate follow-up ( S2 Appendix ) [ 11 , 13 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The protocol, which describes modifications for each version, was first published on 1 April 2020 and amended for this fifth version on 18 June 2021 ( https://osf.io/9ewys/ ). Previous versions have been posted as preprints [ 21 , 23 ] and published as a peer-reviewed article [ 12 ]. We report our findings according to statements on preferred reporting items for systematic reviews and meta-analyses 2020 ( S1 PRISMA Checklist ) [ 24 ] and on synthesis without meta-analysis in systematic reviews (SWiM) [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(24) To address these practical aspects of living systematic reviews, we use our own experience of doing a living systematic review on asymptomatic SARS-CoV-2 infections as a case study. (25) We also draw on covid-19-related living systematic reviews on changes in mental health in the general population, SARS-CoV-2 diagnostics, epidemiology of covid-19 in pregnancy, and effectiveness of treatments and vaccines, which cover a variety of methods used to conduct and manage reviews. (4)(5)(6)(7)(8)(9)(10)(11) In this article, we summarise the characteristics of ongoing living systematic reviews on covid-19, we follow a life cycle approach to describe key steps in a living systematic review, and give recommendations at each step.…”
Section: Introductionmentioning
confidence: 99%